A conceptual model of building maintenance budget determination in the federal common building / Norehan @ Norlida Mohd Noor - Mohd Noor, Norehan @ Norlida (Institute of Graduate Studies, UiTM, 2018)
Budget determination and its appropriate management, has increasingly recognised as a critical issue in many countries, especially in aspect of public building maintenance. Consequently, reformation in building maintenance budget (BMB) determination model become vital, including in Malaysia setting, as well. By taking the BMB determinant-criteria as the focus, this research accentuated the method to create effectiveness, share and exploit the best practice. Taken together, several problems and barriers occurred within budget allocation for public building maintenance has been identified. Through the preliminary survey found that Malaysia is still bound by the 'traditional way', in which classical practice in determining the fund allocation is by 'rough estimates', or using ad hoc budget provided by the Finance Ministry. A generic finding in primary problems promote an idea and triggered an effort to doing this research; to introduce a new approach in the BMB performance. The aim of this research is to investigate the potential and an effective model in determining the accurate prediction of maintenance budget in public building. A fundamental concept for appropriate budget determination model was explored, then the 15 criteria and 34 parameters of budget determinant has carefully selected, collected and filtered. Simultaneously, the investigation against the scenario that hit in the BMB issues are carried out and identified. Case studies were conducted at three (3) zones in the Peninsular Malaysia within selected public buildings known as the Federal Common User's building…